A Deep Dive Analysis of Online Food Delivery with A 6 PS of the Digital Marketing Mix-Based Framework - Narubodee Wathanakom; Nhatphaphat Juicharoen (PT FORMOSA CENDEKIA GLOBAL, 2023)
This paper presents a holistic analysis of OFD by utilizing the 6 Ps of the digital marketing mix to portray how each platform employs strategic marketing to drive sustainable growth. The article utilizes extensive reviews of previous literature, as well as up-to-date news and observations. It was found that each of the market players focused on the product by expanding from only OFD to become lifestyle-driven “everyday apps” by enhancing the UX/UI experiences of the application, which supported and coordinated profound experiences, personalized offerings, and precise data analytics. Price played a role but was not the primary focus since it is controlled by the government to protect consumers. It can be concluded that if an OFD platform would like to grow sustainably, it should place a strong emphasis on product service, quality, and user-friendly technology on the application. Most of the previous studies regarding online food delivery discuss factors in driving adoptions, consumer attitudes and satisfaction towards the application and OFD landscape. There are the gaps in the holistic analyses of OFD from the digital marketing mix framework. Therefore, this academic article is the first to focus on uncovering how each of the top three OFD players in Thailand adopted the digital marketing mix to optimize opportunity.